2009
DOI: 10.4088/jcp.07m03863
|View full text |Cite
|
Sign up to set email alerts
|

Family Problems Among Recently Returned Military Veterans Referred for a Mental Health Evaluation

Abstract: Existing evidence suggests that military veterans with mental health disorders have poorer family functioning, although little research has focused on this topic. Objective: To test whether psychiatric symptoms are associated with family reintegration problems in recently returned military veterans. Design: Cross-sectional survey of a clinical population. Respondents who were referred to behavioral health evaluation from April 2006 through August 2007 were considered for the survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
338
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(356 citation statements)
references
References 38 publications
13
338
2
3
Order By: Relevance
“…Among Army families with children 3.5 years old or younger, parent stress was related to child behavior problems (Barker and Berry 2009). These effects appear to persist among OEF/OIF/OND veterans referred for mental health evaluations over a year post-deployment, on average (Sayers et al 2009); among these veterans, 78 % reported a family concern, including having a troubled relationship (58 %), having disagreements about responsibilities (57 %), feeling like a guest within the family (41 %), being unsure of responsibilities (37 %), and children being afraid or not warm toward the veteran.…”
Section: Current Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Among Army families with children 3.5 years old or younger, parent stress was related to child behavior problems (Barker and Berry 2009). These effects appear to persist among OEF/OIF/OND veterans referred for mental health evaluations over a year post-deployment, on average (Sayers et al 2009); among these veterans, 78 % reported a family concern, including having a troubled relationship (58 %), having disagreements about responsibilities (57 %), feeling like a guest within the family (41 %), being unsure of responsibilities (37 %), and children being afraid or not warm toward the veteran.…”
Section: Current Eramentioning
confidence: 99%
“…In a study of active duty military families affected by OEF/OIF/OND deployments either currently or within the prior 12 months, service member PTSD symptoms were associated with child depression, internalizing behaviors, and externalizing behaviors in children ages 6-to 12 years old (Lester et al 2010). Among married/partnered OEF/OIF/OND veterans referred for a mental health evaluation, PTSD was associated with children's fear of or emotional distance from the veteran (Sayers et al 2009). In this same study, the avoidance and emotional numbing PTSD clusters were associated with having at least one role-related family problem.…”
Section: Current Eramentioning
confidence: 99%
“…Specifically, PTSD is associated with impairments in occupational and academic functioning [2][3][4][5][6], marital and family functioning [5,[7][8], parenting [9][10], and friendships and socializing [11]. Additional studies have shown associations between PTSD and objective indicators of quality of life (QOL) such as homelessness and unemployment [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have shown associations between PTSD and objective indicators of quality of life (QOL) such as homelessness and unemployment [12][13]. Such impairments are common among populations at high risk for PTSD, such as military personnel deployed to combat [3,[5][6][8][9][10][11][12][13][14]. Research suggests that these impairments are currently affecting many Veterans of the wars in Iraq and Afghanistan (Operations Iraqi Freedom and Enduring Freedom) and are therefore important to identify and treat [15].…”
Section: Introductionmentioning
confidence: 99%
“…Servicemembers who report family problems, either before or after a deployment, are at greater risk for PTSD [1]. Also, PTSD symptoms have been found to have a negative effect on readjustment, leading to difficulties with reestablishing bonds, familial roles, and household routines [2][3]. Altogether, research highlights the importance of a postdeployment environment in which family members are able to adequately understand, communicate with, and support servicemembers experiencing PTSD and other postdeployment sequelae.…”
Section: Introductionmentioning
confidence: 99%